Laser Techniques for reshaping the Cornea (Eurasian Journal of Research, Development and Innovation, 2024)
The shape of the cornea of the eye can be modified to correct permanently for nearsightedness or far-sightedness. Heat energy can be delivered to the cornea for this purpose in order to elevate the collagen in mid-cornea to its shrinkage temperature of about 60 °C. When a suitable pattern of shrinkage is created in the peripheral cornea, the central cornea may steepen or flatten in response, and this change in curvature may serve as a refractive correction